(untitled) (Superficies y Vacío, 2017)
A modular and generic, monolithic integrated MEMS fabrication process is presented to integrate microelectronics (CMOS) with mechanical microstructures (MEMS). The proposed monolithic integrated fabrication process is designed using an intra-CMOS approach (to fabricate the mechanical microstructures into trenches without the need of planarization techniques) and a CMOS module (to fabricate the electronic devices) with a 3 ?m length as minimum feature. The microstructures module is made up to three polysilicon layers, and aluminum as electrical interconnecting material. From simulation results, using the SILVACO® suite (Athena and Atlas frameworks), no significant degradation on the CMOS performance devices was observed after MEMS manufacturing stage; however, the thermal budget of the modules plays a crucial role, because it set the conditions for obtaining the complete set of devices fabricated near their optimal point. Finally, to evaluate and to support the development of the proposed integrated MEMS process, a modular test chip that includes electrical test structures, mechanical test structures, interconnection reliability test structures and functional micro-actuators, was also designed.